Role of the Green Supply Chain on Improving the Quality of Hotels Services: A Field Study in the Hotels of the Capital City of Sana'a - Jamal Nasser Ali Al-Kamim; Nada Gamil Ahmed Saleh Al-Saidi (University of Science and Technology, Sana’a, Yemen, 2023)
This study aimed to investigate the impact of green supply chains on the enhancement of hotel service quality within the hotels of the capital city of Sana’a. Furthermore, the research sought to examine the adjusted role of hotel size in influencing the relationship between green supply chain management and the quality of hotel services. To accomplish these objectives, a descriptive-analytical approach was employed. The data was collected by a questionnaire. A total sample of 313 individuals was selected randomly from a population of (1214). The data analysis was conducted using the partial least squares structural equation modeling (PLS-SEM) technique with the Smart PLS software, as well as the Statistical Package for the Social Sciences (SPSS). The findings of the study revealed a statistically significant role played by green supply chains in improving the quality of hotel services in Sana'a. Additionally, the study underscored that the size of the hotel moderates the relationship between the management of green supply chains and the quality of hotel services.